The Effect of Futures Markets on the Financial and Behavioral Approach of Accepted Companies in Tehran Stock Exchange - GANDOMAN, Shaho Heidari; NAZARIPOUR, Mohammad; ROSTAMI, Mohammad; CHAVOSHI, Omid (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The purpose of this study was to investigate the effect of futures markets on the financial-behavioral approach of listed companies in Tehran Stock Exchange. The statistical population is the unlimited number of investors and 384 investors in the companies admitted to the Tehran Stock Exchange. The results showed that behavioral taxes had a significant impact on futures contracts and future futures contracts, Iran's futures contract in the future contract for the second contract at the third rate of the contract and the future contract at fourth and late, and the least impact on Comparison with other dimensions in the behavioral financial approach.